Remarkable observations of melanistic leopard (Panthera pardus pardus) in Nepal - Koju, Narayan Prasad; Byanjankar, Saraswati; Thapa, Deepa; Shrestha, Sandhya; Thapa Magar, Ashim; Chalise, Lina; Shrestha, Arati; Bhandari, Ram Kumar (Nepalese Journal of Zoology, 2022)
Melanism has been reported in many mammals, but records of melanistic leopards in Nepal are very few and not systematic, even though common leopards are found throughout the country and are considered one of the most problematic carnivores. In this study, we gathered data on records of five melanistic leopards that were seen or caught close to the Kathmandu Valley. Out of the five, two were captured on camera by locals, two were records of animals that were found alive but suffered injuries and passed away in captivity, and one was a record of a dead animal. All of them were recorded close to human populated areas. It is unknown what causes a high occurrence of melanosis in leopards and why it frequently occurs close to the Kathmandu Valley. It is recommended to conduct a comprehensive analysis of their population, geographic range, and habitat.